Meninjau Ulang Asbabun Nuzul Surat Al-Taubah Ayat 75 - idris idris (LPPM Institut Pesantren KH. Abdul Chalim, 2018)
This paper discusses the history of the story of Sa'labah bin Hatib which is ascribed to asbabun nuzul from surat al-Taubah verse 75. Most commentators refer to the history of al-Tabari. Two narrations of al-Tabari index number 16986 and 16987, each base of the sanad ends in Ibn nu Abbas's friend and Abu Umamah al-Bahili. The majority of hadith critics say that most of the narrators in the chain of the second sanad of al-Tabari's history are punished by da'if and munkar. From the side of the law, there are also many irregularities, including: 1) contrary to surat al-Taubah verse 103 which instructs to take zakat. 2) Contrary to the next zahir verse, namely verses 76 and 77 of surat al-Taubah. 3) Contrary to the historical fact, the hypocrites were reluctant to pay zakat fought by Abu Bakr.